2018
DOI: 10.1128/mmbr.00015-18
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Recognition of Microbes and Pathogens: Inflammasomes in Action

Abstract: Infection is a dynamic biological process underpinned by a complex interplay between the pathogen and the host. Microbes from all domains of life, including bacteria, viruses, fungi, and protozoan parasites, have the capacity to cause infection. Infection is sensed by the host, which often leads to activation of the inflammasome, a cytosolic macromolecular signaling platform that mediates the release of the proinflammatory cytokines interleukin-1β (IL-1β) and IL-18 and cleavage of the pore-forming protein gasd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 461 publications
(546 reference statements)
3
112
0
1
Order By: Relevance
“…Several bacterial molecules can serve as signal 2 during activation of NAIPs (Figure ) (Hayward et al, ; Evavold & Kagan, 2019). Bacterial flagellin and evolutionarily conserved rod and needle proteins of the type 3 secretion system (T3SS) injectisome of some Gram‐negative bacteria are recognised by the NAIPs, leading to the assembly of the NLRC4 inflammasome in macrophages (Miao, Mao, et al, ; Zhao et al, ).…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several bacterial molecules can serve as signal 2 during activation of NAIPs (Figure ) (Hayward et al, ; Evavold & Kagan, 2019). Bacterial flagellin and evolutionarily conserved rod and needle proteins of the type 3 secretion system (T3SS) injectisome of some Gram‐negative bacteria are recognised by the NAIPs, leading to the assembly of the NLRC4 inflammasome in macrophages (Miao, Mao, et al, ; Zhao et al, ).…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
“…Several bacterial molecules can serve as signal 2 during activation of NAIPs ( Figure 1) (Hayward et al, 2018;Evavold & Kagan, 2019).…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviruses are non‐enveloped dsDNA viruses that commonly cause respiratory infections in humans. Previous studies observed that adenovirus infection of myeloid cells could cause inflammasome activation, but the mechanism and nature of the inflammasome sensor involved were not clearly defined (Hayward et al , ; Labzin et al , ). Notably, the impact of anti‐adenovirus antibodies, which are likely to be present in a natural infection, on macrophage sensing of adenovirus was unknown.…”
Section: Trim21 Triggers Nlrp3 Activation In Response To Adenovirus Imentioning
confidence: 99%
“…Select cytosolic PRRs such as NLRP3 and AIM2 form inflammasomes, protein complexes which mediate the activation of the zymogen protease caspase-1. Caspase-1 cleaves the pro-inflammatory cytokines pro-IL-1b and pro-IL-18, triggering their secretion, and also cleaves gasdermin-D resulting in plasma membrane pore formation and inflammatory cell death called pyroptosis (Broz & Dixit, 2016;Hayward et al, 2018). Inflammasome-dependent secretion of IL-1b and IL-18 drives both innate and adaptive immune responses (Evavold & Kagan, 2018;Hayward et al, 2018).…”
mentioning
confidence: 99%